2004
DOI: 10.1088/1475-7516/2004/08/006
|View full text |Cite
|
Sign up to set email alerts
|

Supernova constraints on a holographic dark energy model

Abstract: In this paper, we use the type Ia supernova data to constrain the model of holographic dark energy. For d = 1, the best fit result is Ω 0 m = 0.25, the equation of the state of the holographic dark energy w 0 Λ = −0.91 and the transition between the decelerating expansion and the accelerating expansion happened when the cosmological red-shift was z T = 0.72.If we set d as a free parameter, the best fit results are d = 0.21, Ω 0 m = 0.46, w 0 Λ = −2.67, which sounds like a phantom today, and the transition reds… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
185
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(214 citation statements)
references
References 23 publications
27
185
2
Order By: Relevance
“…Recently, some constraints from SNe Ia on related model where obtained in Refs. [16,17]. In this paper, we extend the analysis carried out in Ref.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Recently, some constraints from SNe Ia on related model where obtained in Refs. [16,17]. In this paper, we extend the analysis carried out in Ref.…”
Section: Introductionmentioning
confidence: 57%
“…Some speculations on the deep reasons of the holographic dark energy were considered by several authors [14]; further studies on this model see also [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…We assumed two different phases of HDE model i.e., quintessence regime (c 1) and phantom regime (c < 1). In the case of phantom regime, we adopted the constrained value for the model parameter c = 0.815 obtained in Enqvist & Sloth (2004); Gong (2004); Huang & Gong (2004b); Huang & Li (2004); Li et al (2009). We first investigated the growth of structures in linear regime and showed that the growth of density perturbations g(a) is slowed down in HDE models compared to the EdS and ΛCDM models due to a larger Hubble parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Using recent observational data, the value of the holographic parameter c in a flat Universe was constrained to c = 0.815 +0.179 −0.139 (Enqvist & Sloth 2004;Gong 2004;Huang & Gong 2004b;Huang & Li 2004;Li et al 2009). The cosmic coincidence problem can be solved by inflation in HDE model (Li 2004).…”
Section: Cosmology With Holographic Dark Energymentioning
confidence: 99%
“…We shall focus on the DE model inspired by the holographic idea that the energy within our horizon cannot exceed the mass of a black hole of the same size [26,27,28]. The extension of the holographic principle to a general cosmological setting was first addressed by Fischler and Susskind [29] and subsequently got modified by many authors [30]- [34].…”
mentioning
confidence: 99%